Avian temporal diversity assessment in Pangsun, Selangor - Farah Shafawati, . (Department of Wildlife and National Parks - Perhilitan, 2009)
Due to the rising need of effective conservation strategies around the world, biodiversity monitoring or assessment has been one of the main concerns. Biodiversity residing in specific habitat is the best indicator of the habitat condition regardless of species diversity changes or their health condition. This information, combining with ecological condition of the habitat will provide sound knowledge for future conservation and research activities. Therefore, we came out with a small scale temporal biodiversity assessment at Pangsun, Hulu Langat forest reserve for a start, but concentrating on avian diversity only. Data were compiled from thesis, reports, proceedings, and published papers from various institutions. We were able to gather data from 1993 to 2011. From this compilation there were 66 bird species from 8 orders, and 23 families recorded from all years. This numbers comprised of only 26% of species recorded by Siti Hawa in her preliminary survey in Hulu Langat Forest Reserve in 1983. The most dominant families were Timaliidae (babblers) with 12 species, followed by Turdidae (Thushers, Robin, Forktail, shama) with 8 species. Species richness was found to increase temporally which shows good habitat condition of the study area. There were several species recorded in all years which were the Ceyx erithacus (oriental Dwarf kingfisher), Arachnothera longirostrq (Little spiderhunter) and stachyris nigriceps (Grey-throated babbler). However, some of the forest birds that have been recorded previously were no longer present in the latest monitoring data suggesting that this forest is slowly loosing precious bird species some of which are listed as vulnerable (VU) and near-threatened (NT). Thus, these species can be an indicator of habitat changes. Nevertheless, Cacomantis sepulcralir (Rusty-breaste d cuckoo), Ficedula suspecilliaris (Ultramarine flycatcher) and Arachnothera affinis (Streaky-breasted spiderhunter) were among the species that appear in the later year and never been recorded in the study area before.